Perlindungan Hukum bagi Penyandang Disabilitas dalam Angkutan Udara - Priscila; Ni Luh Made Mahendrawati; I Ketut Sukadana (Warmadewa Press, 2021)
Transportation is currently divided into three types, namely land transportation, sea transportation and air transportation. Nowadays, many people prefer to use air transportation since air transportation can travel long distances in a relatively shorter time. However, it is not infrequently for airlines to cause losses to consumers, especially to people with disabilities. Where as fact people with disabilities should get special treatment. Therefore, these problems can be examined as follows: 1) how is the legal protection for people with disabilities in the positive law in Indonesia? 2) What is the regulation of the rights of consumers with disabilities as airplane passengers? This presentation used normative research methods to find whether there are legal rules according to legal norms or not, whether there are norms in the form of orders or prohibitions in accordance with legal principles or not and whether one’s actions are in accordance with legal norms or not by using a legal and conceptual approach. This research required a source of secondary legal material as the main legal material. People with disabilities have the right to receive special services and facilities while at an airport or aircraft. The government has made legislation as a form of legal protection for people with disabilities. Nevertheless, the government must be more assertive in order to avoid discrimination against people with disabilities. Furthermore, it is not only the government that must provide legal protection for people with disabilities but also the community. The community must change the mindset about people with disabilities who are considered unable to do anything, and they must help people with disabilities to get equal treatment before the law.